Pemodelan Dinamis Distributed Lag Dengan Menggunakan Metode Koyck Dan Metode Almon - Dora Panny Nurcahaya Sitorus; Widiarti Widiarti; Agus Sutrisno; Mustofa Usman (FMIPA Universitas Lampung, 2023)
The distributed lag Model is a dynamic model due to the effect of a one-unit change in the value of the distributed independent variable (X) over a period of time. Distributed lag Model there are 2 types, namely: infinite lag model and finite lag model. Infinite lag modeling using koyck method and finite lag modeling using Almon method. This distributed lag Model is used to visualize the impact caused by the independent variable on the dependent variable. This study aims to apply a dynamic model of distributed lag by using the koyck transformation method and Almon transformation method to assess the effect of the rupiah exchange rate on the value of garment exports PT. Shinwon went abroad and determined the best model in Dynamic Modeling of distributed lag using the koyck transformation method and the Almon transformation method. The results showed that dynamic modeling of distributed lag with Almon transformation method is better than koyck transformation.